Pest categorisation of Euzophera semifuneralis - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2023)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Euzophera semifuneralis (Lepidoptera: Pyralidae), the American plum borer for the EU. This insect is native to North America, reported from the United States, Canada and Mexico. Out of its native range it is only present in Türkiye. It has not been reported in the EU and is not listed in Annex II of Commission Implementing Regulation (EU) 2019/2072. It can complete from one up to three generations per year in its native range and is polyphagous, feeding on 22 genera in 16 plant families. Host plant species commonly found in the EU include black walnut (Juglans nigra), mulberry (Morus alba, M. nigra), olive (Olea europaea), almond (Prunus dulcis), apricot (P. armeniaca), peach (P. persica), plum (P. domestica), sweet cherry (P. avium), apple (Malus domestica), pear (Pyrus communis) and pomegranate (Punica granatum). E. semifuneralis is generally known as pest of trees affected by mechanical injuries, frost or canker diseases. The pest is also known to vector the fungus Ceratocystis fimbriata which is not known to occur in the EU. Climatic conditions and availability of host plants in some EU countries would allow this species to establish and spread. Impact in cultivated hosts including apples, plums, mulberries, almond, olive and ornamental broadleaf trees is anticipated. Phytosanitary measures are available to reduce the likelihood of entry and spread. E. semifuneralis meets the criteria that are within the remit of EFSA to assess for this species to be regarded as a potential Union quarantine pest.